2011
DOI: 10.4155/bio.11.172
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an LC–MS/MS Assay for Detecting Relevant Disaccharides from Keratan Sulfate as a Biomarker for Morquio A Syndrome

Abstract: Clinical sample analysis in 168 MPS IVA patients and 225 healthy controls demonstrates the clinical utility of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…It was observed that urine KS levels decrease with age ( Supplementary Fig. 1), as has been previously observed by Martell et al (2011). This phenomenon was also observed for GAGs (de Jong et al 1989;Whitley et al 1989;Piraud et al 1993;Gray et al 2007;Wood et al 2012).…”
Section: Establishing Normal Reference Rangessupporting
confidence: 70%
See 3 more Smart Citations
“…It was observed that urine KS levels decrease with age ( Supplementary Fig. 1), as has been previously observed by Martell et al (2011). This phenomenon was also observed for GAGs (de Jong et al 1989;Whitley et al 1989;Piraud et al 1993;Gray et al 2007;Wood et al 2012).…”
Section: Establishing Normal Reference Rangessupporting
confidence: 70%
“…Previous reports have documented the age-dependent decrease in keratan sulfate levels (de Jong et al 1989;Whitley et al 1989;Piraud et al 1993;Gray et al 2007;Martell et al 2011;Wood et al 2012). However, these studies had a limited number of samples for patients under the age of 3 years.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similar methods have been validated in another laboratory (Martell et al 2011). KS levels in blood and urine in patients with MPS IVA are associated with age and clinical severity (Tomatsu et al 2010c) and are decreased with enzyme replacement therapy (ERT) on mouse model and bone marrow transplantation (BMT) in a patient with MPS IVA Chinen et al 2014).…”
Section: Introductionmentioning
confidence: 99%